Interrogating artificial agency - Wong, Hong Yu (Frontiers in Psychology, 2025)
Can artificial systems act? In the literature we find two camps: sceptics and believers. But the issue of whether artificial systems can act and, if so, how, has not been systematically discussed. This is a foundational question for the philosophy of AI. I sketch a methodological approach to investigating the agency of artificial systems from architectural and behavioural perspectives.